SUMMARY OF NEGOTIATIONS ON THE SEARCH FOR A SOLUTION TO THE PROBLEM OF" POVERTY REDUCTION" (Conferencea, 2023)
This article will talk about the positive and negative results that have been achieved so far and at the same time during experiments on poverty reduction, increase in jobs, and about the disputes over plans to solve this problem further.